Tobacco smoking and cytokine levels in human epicardial adipose tissue: Impact of smoking cessation - Mach, Lukas; Bedanova, Helena; Soucek, Miroslav; Karpisek, Michal; Nemec, Petr; Orban, Marek (Atherosclerosis, 2016)
BACKGROUND & AIMS: Epicardial adipose tissue (EAT) is a source of a number of cytokines which could act in the pathogenesis of coronary artery disease (CAD). The potential relationship between known cardiovascular risk factors, such as smoking, dyslipidaemia or diabetes mellitus and EAT humoral signalling, has not been fully elucidated. Therefore, we designed and conducted a cross-sectional study to determine whether selected cardiovascular risk factors are linked to levels of cytokines in epicardial and subcutaneous adipose tissue (SAT). METHODS: Samples of SAT and EAT were collected from consecutive patients undergoing scheduled cardiac surgery. Tissue concentrations of tumour necrosis factor-ɑ (TNF-α), interleukin-6 (IL-6), adipocyte fatty acid-binding protein, leptin, and adiponectin were determined by ELISA. RESULTS: We enrolled 140 patients. TNF-α and IL-6 concentrations in EAT and SAT were significantly higher in current smokers (CS) than in never smokers (NS) and former smokers (FS). There were no differences between FS and NS. No other clinical variables were associated with cytokine concentrations in a regression analysis. CONCLUSIONS: Smoking was independently associated with higher TNF-α and IL-6 concentrations in EAT and SAT. A novel observation that pro-inflammatory cytokines are elevated in EAT in smokers could contribute to identify potential mechanisms involved in the pathogenesis of adverse effects of tobacco smoking. There were no differences between EAT cytokine production in NS and FS, which support the importance of smoking cessation for cardiovascular risk reduction.
Keywords: senioři; kouření; Cross-Sectional Studies; Up-Regulation; Inflammation; Subcutaneous Fat; interleukin-6; prevence kouření; upregulace; mediátory zánětu; Interleukin-6; Tumor Necrosis Factor-alpha; podkožní tuk; Smoking Prevention; Middle Aged; mužské pohlaví; Coronary artery disease; Pericardium; průřezové studie; Cytokines; Inflammation Mediators; TNF-alfa; Smoking Cessation; Smoking; ženské pohlaví; Humans; Epicardial adipose tissue; lidé středního věku; perikard; Female; Aged; odvykání kouření; lidé; Male